2003
DOI: 10.3168/jds.s0022-0302(03)73809-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relationships among Body Condition Score, Body Weight, Milk Yield, and Fertility in Dairy Cows

Abstract: Genetic (co)variances between body condition score (BCS), body weight (BW), milk production, and fertility-related traits were estimated. The data analyzed included 8591 multiparous Holstein-Friesian cows with records for BCS, BW, milk production, and/or fertility from 78 seasonal calving grass-based farms throughout southern Ireland. Of the cows included in the analysis, 4402 had repeated records across the 2 yr of the study. Genetic correlations between level of BCS at different stages of lactation and total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

58
249
15
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 277 publications
(333 citation statements)
references
References 34 publications
58
249
15
11
Order By: Relevance
“…The low heritability of the traditional fertility traits in the present study corroborates the many previous studies on genetic parameters for traditional fertility measures (Pryce and Veerkamp, 2001;Berry et al, 2003;Wall et al, 2003). The heritability estimates of CFH and CFS, however, are slightly larger than that generally observed from field data, which may be attributable to an expected greater accuracy of recording in experimental herds.…”
Section: Genetic Parameterssupporting
confidence: 89%
See 2 more Smart Citations
“…The low heritability of the traditional fertility traits in the present study corroborates the many previous studies on genetic parameters for traditional fertility measures (Pryce and Veerkamp, 2001;Berry et al, 2003;Wall et al, 2003). The heritability estimates of CFH and CFS, however, are slightly larger than that generally observed from field data, which may be attributable to an expected greater accuracy of recording in experimental herds.…”
Section: Genetic Parameterssupporting
confidence: 89%
“…influenced by a large or small number of genes). Large population sizes for genome-wide association analysis are required for lower heritability traits such as traditional measures of fertility (Pryce and Veerkamp, 2001;Berry et al, 2003;Wall et al, 2003); this can be somewhat overcome by using fertility-estimated breeding values on genotyped sires as the phenotype under investigation; nonetheless, phenotypes on a large number of cows are still required to generate accurate sire-estimated breeding values. The low heritability of fertility traits can be due to a multitude of factors including: (1) the trait is truly under poor additive genetic control relative to non-additive and non-genetic factors; (2) the statistical model used to estimate the variance components is too simplistic relative to reality; (3) recording errors adding to random noise; and (4) preferential treatment that cannot be fully accounted for in the statistical model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary results (lactations 1 and 2) presented by Begley et al (2009) demonstrated a clear fertility advantage with both pure Norwegian Red and F1 crossbreds (Norwegian Red × Holstein-Friesian). Body condition score, a trait genetically associated with differences in reproductive efficiency (Berry et al, 2003), was recorded during May/early June 2006 to represent body condition at breeding, was higher (P < 0.001) with the Norwegian Red at 3.03 compared with the HolsteinFriesian at 2.85. The BCS of that of the F1 (2.98) cows was similar to the Norwegian Red but higher (P < 0.001) than the Holstein-Friesian.…”
Section: Crossbreeding Research In Irelandmentioning
confidence: 99%
“…factors that effect the performance of an animal over its lifetime) usually account for more variation in performance among animals than additive genetic effects (Berry et al, 2003). Currently little is known about the biological process(es) contributing to these permanent environmental effects, and little research has been done to attempt to exploit such effects in animal breeding.…”
Section: Challenges and Future Researchmentioning
confidence: 99%